Nutrients and chemical oxygen demand (COD) removals by microalgae - bacteria co-culture system in palm oil mill effluent (POME) - Samsudin, Amirah; Azmi, Azlin Suhaida; Mohd Nawi, Mohd Nazri; Abdul Halim, Amanatuzzakiah (IIUM Journal Publication Unit, 2019)
In Malaysia, large amounts of waste known as palm oil mill effluent (POME) are generated during the production process of crude palm oil. Conventionally, POME is treated using biological treatment that involves two processes; aerobic and anaerobic. These processes however, require long hydraulic retention time and produce methane and carbon dioxide (CO2) that can cause environmental problems. Alternatively, POME can be treated by a combination of microalgae and bacterial co-culture that requires a shorter treatment time and is environmentally friendly. In this study, a microalgae strain, Chlorella vulgaris was co-cultured with a bacteria strain Azospirillum brasilense in POME with an initial concentration of 1.9´106 cells/mL and 104 CFU/mL, respectively. The removal of chemical oxygen demand (COD) and nutrients (phosphorus and ammonium) were analyzed using Standard Methods, APHA 1999. The effectiveness of the co-culture system in POME treatment under agitation and aeration conditions for nutrients and COD removals were studied. Results show that the removal of ammonium by microalgae was much higher under the aeration condition (73.5%) compared to that of the agitation condition (34.4%) in POME. Moreover, co-culture system exhibits better removal of ammonium, phosphorus, and COD (84%, 87.3% and 51.8%, respectively) compared to that in an axenic microalgae system (67%, 84.2% and 41.1%, respectively). The kinetic studies on the co-culture system and the nutrients removal were also conducted. The kinetic coefficients of maximum specific growth rate (µmax) and half-saturation coefficient (ks) obtained from Lineweaver-Burk plot were 0.192 d?1 and 27.32 mg/L, respectively. Based on the findings obtained, the co-culture system could be implemented as an efficient and inexpensive alternative method for POME treatment.